Acute gastroenteritis and enteric viruses in hospitalised children in southern Brazil: aetiology, seasonality and clinical outcomes - Sonia Maria Raboni (Memórias do Instituto Oswaldo Cruz., 2014)
Viral acute gastroenteritis (AG) is a significant cause of hospitalisation in children younger than five years. Group A rotavirus (RVA) is responsible for 30% of these cases. Following the introduction of RVA immunisation in Brazil in 2006, a decreased circulation of this virus has been observed. However, AG remains an important cause of hospitalisation of paediatric patients and only limited data are available regarding the role of other enteric viruses in these cases. We conducted a prospective study of paediatric patients hospitalised for AG. Stool samples were collected to investigate human adenovirus (HAdV), RVA, norovirus (NoV) and astrovirus (AstV). NoV typing was performed by nucleotide sequencing and phylogenetic analysis. From the 225 samples tested, 60 (26%) were positive for at least one viral agent. HAdV, NoV, RVA and AstV were detected in 16%, 8%, 6% and 0% of the samples, respectively. Mixed infections were found in nine patients: HAdV/RVA (5), HAdV/NoV (3) and HAdV/NoV/RVA (1). The frequency of fever and lymphocytosis was significantly higher in virus-infected patients. Phylogenetic analysis of NoV indicated that all of these viruses belonged to genotype GII.4. The significant frequency of these pathogens in patients with AG highlights the need to routinely implement laboratory investigations.